Marxism, Religion, and Emancipatory Politics - Kirkpatrick, Graeme; McMylor, Peter; Fadaee, Simin (Marx, Engels, and Marxisms, 2022)
1. Theology after Marxism -- 2. Marxism, theology and the meanings of ‘critique’ -- 3. Secular Redemption -- 4. Marxism and Buddhism: A History and Appraisal -- 5. Marxism and Sikhism: A reciprocal relationship -- 6. Marxism and the question of ‘political religions’: can Marxism be understood as a religious phenomenon? -- 7. Zapatismo and Theology of Liberation -- 8. Liberation Theology and Non-Dogmatic Marxism in the Philippines -- 9. From Freedom of Religion to Environmentalism and Democracy: Understanding the Political Praxis of Christian Activists in the Communist Party-State Vietnam -- 10. Marxism and Confucianism in China -- 11. The (im)possibilities of a Hindu Left in contemporary India -- 12.The Popular Movement of the Rif; towards a class analysis of popular Islam in the contemporary Maghreb -- 13. Marxism, Islam and the Iranian Revolution -- 14. Political Islam as Counterhegemony: The Muslim Brotherhood and the Limits of Appropriating Gramsci to the Egyptian Context.